Polemik Tes Wawasan Kebangsaan Komisi Pemberantasan Korupsi: Analisis Perspektif Hukum - Pranita, Putri Adisty (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
Komisi Pemberantasan Korupsi (KPK) is an Indonesian government institution that is independent, impartial and not subject to any authority. This organization was formed to strengthen efforts to eradicate corruption. The aim of this research is to determine the level of tolerance of the polemic of the national insight test applied at the Corruption Eradication Committee through legal perspective analysis. This research will only outline the legal position on the problem studied. Therefore, this research is categorized as doctrinal research. Data collection uses the literature review method. The results of this research have several analyzes which produce the conclusion that TWK in independent institutions such as the KPK is very restrictive and also too artificial. Apart from analyzing the legal perspective, the polemic that occurred at the KPK institution can be analyzed from other perspectives.